Экспонат руками не трогать: [роман] / Мария Очаковская - Очаковская Мария Анатольевна (Татьяна Устинова рекомендует, 2016)
Экземпляры: Аб (20160926) / Инвентарный номер: 44777 / Цена: / Авт.знак: О-94 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6